2013
DOI: 10.5005/jp-journals-10024-1301
|View full text |Cite
|
Sign up to set email alerts
|

Use of Clinical Bleaching with 35% Hydrogen Peroxide in Esthetic Improvement of Fluorotic Human Incisors in vivo

Abstract: In very mild and mild forms of fluorosis, in-office vital tooth bleaching with 35% hydrogen peroxide is the most conservative and effective approach in esthetic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Our findings are in accordance with Knoesel et al who found that a single 1‐hour session of in‐office bleaching with 30% hydrogen peroxide does not significantly affect the color and luminosity of fluorotic teeth and these changes were found to be in accordance with the patients' recorded self‐perception scales . Further Shanbhag et al compared the effects of bleaching with 35% H 2 O 2 among different grades of fluorosis and found better immediate shade improvement in moderate fluorosis as compared to milder cases . However, our inclusion criteria included all the cases of mild to moderate fluorosis (TF scores 1–4), hence the overall results might have been less esthetic.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in accordance with Knoesel et al who found that a single 1‐hour session of in‐office bleaching with 30% hydrogen peroxide does not significantly affect the color and luminosity of fluorotic teeth and these changes were found to be in accordance with the patients' recorded self‐perception scales . Further Shanbhag et al compared the effects of bleaching with 35% H 2 O 2 among different grades of fluorosis and found better immediate shade improvement in moderate fluorosis as compared to milder cases . However, our inclusion criteria included all the cases of mild to moderate fluorosis (TF scores 1–4), hence the overall results might have been less esthetic.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding DF, 8 of the selected studies assessed the bleaching of the affected teeth, 9 analyzed the effects of enamel microabrasion, 4 evaluated the effect of a combined treatment (tooth bleaching and enamel microabrasion) and Gugnani et al used a resin infiltrant. Gupta et al and Mehta et al studied the effect of oral administration of calcium and vitamins in reducing lesion size whereas Hasanuddin et al applied fissure sealants to molars with DF.…”
Section: Resultsmentioning
confidence: 99%
“…All authors analyzed the effectiveness of the treatments through a visual evaluation. Of these, 14 resorted to photographs and 2 used a chromameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bleaching effect is achieved due to oxidative action of peroxides and its sub-products on the organic matrix of the tooth tissues modifying its optical properties (6,7). Despite the high success rates observed for both in-office and athome bleaching procedures (4,5), using oxidative agents are unable to solve aesthetic alterations of teeth when the discoloration is intrinsic in the enamel due to fluorosis staining and other enamel hypoplasia, or white lesion spot caused by dental caries (8,9).…”
Section: Introductionmentioning
confidence: 99%